The Ukraine Support Tracker: Which countries help Ukraine and how? - Christoph Trebesch; Arianna Antezza; Katelyn Bushnell; André Frank; Pascal Frank; Lukas Franz; Ivan Kharitonov; Bharath Kumar; Ekaterina Rebinskaya; Stefan Schramm (Kiel Institute for the World Economy (IfW Kiel), 2023)
This paper presents the "Ukraine Support Tracker", which lists and quantifies military, financial and humanitarian aid to Ukraine in the context of Russia's war against Ukraine. We track government commitments to Ukraine made between January 24, 2022 and January 15, 2023 by 40 governments plus the EU institutions. We find significant differences in the scale of support across countries, both in absolute terms and as percent of donor country GDP. In billions of Euros, by far the largest single bilateral supporter of Ukraine is the United States, followed by the EU institutions, the United Kingdom, and Germany. In percent of donor GDP, Eastern European countries stand out as particularly generous and even more so once we account for refugee costs. In comparison to previous wars in history, the support for Ukraine is small, especially when considering the size of donor GDP. Annual US spending during the Korea, Vietnam and Iraq wars, for example, was much higher compared to spending on Ukraine 2022. Germany's support to liberate Kuwait during the Gulf War 1990/91 also far exceeds its help for Ukraine in 2022. Moreover, we find that Western countries clearly prioritized their own population in recent months. EU governments mobilized 10 times more funds for new domestic energy subsidies compared to what they mobilized for Ukraine. Thus, in the bigger picture, the international support for Ukraine so far has been rather limited.
Additional information: This is a considerably expanded version of the original paper and database (9th update). We are continuously improving this project and welcome feedback to ukrainetracker@ifw-kiel.de. We are greatly indebted to hundreds of readers around the world who have sent us helpful comments and suggestions. https://www.ifw-kiel.de/topics/war-against-ukraine/ukraine-support-tracker/
Keywords: F35; F51; H56; H63; H84; H81; 330; International aid; military aid; war; geoeconomics